Rapid Ammonia Gas Transport Accounts for Futile Transmembrane Cycling under NH(3)/NH(4)(+) Toxicity in Plant Roots(1)([C])([W]) - Coskun, Devrim (American Society of Plant Biologists, 2013)
Futile transmembrane NH(3)/NH(4)(+) cycling in plant root cells, characterized by extremely rapid fluxes and high efflux to influx ratios, has been successfully linked to NH(3)/NH(4)(+) toxicity. Surprisingly, the fundamental question of which species of the conjugate pair (NH(3) or NH(4)(+)) participates in such fluxes is unresolved. Using flux analyses with the short-lived radioisotope (13)N and electrophysiological, respiratory, and histochemical measurements, we show that futile cycling in roots of barley (Hordeum vulgare) seedlings is predominately of the gaseous NH(3) species, rather than the NH(4)(+) ion. Influx of (13)NH(3)/(13)NH(4)(+), which exceeded 200 µmol g(–1) h(–1), was not commensurate with membrane depolarization or increases in root respiration, suggesting electroneutral NH(3) transport. Influx followed Michaelis-Menten kinetics for NH(3) (but not NH(4)(+)), as a function of external concentration (K(m) = 152 µm, V(max) = 205 µmol g(–1) h(–1)). Efflux of (13)NH(3)/(13)NH(4)(+) responded with a nearly identical K(m). Pharmacological characterization of influx and efflux suggests mediation by aquaporins. Our study fundamentally revises the futile-cycling model by demonstrating that NH(3) is the major permeating species across both plasmalemma and tonoplast of root cells under toxicity conditions.